2014
DOI: 10.1089/ten.tea.2012.0726
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Bone Regeneration Capability of Ceramic Scaffolds by Accelerated Release of Their Calcium Ions

Abstract: To regenerate the bone tissue, the fabrication of scaffolds for better tissue regeneration has attracted a great deal of attention. In fact, growth factors are already used in clinical practice and are being investigated for enhancing the capacity for bone tissue regeneration. However, despite their strong osteoinductive activity, these growth factors have several limitations: safety issues, high treatment costs, and the potential for ectopic bone formation. The aim of this study was therefore to develop ceram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 37 publications
1
50
1
1
Order By: Relevance
“…Previous studies have reported a significant increase in calcium ion release and subsequent osteoclast-mediated resorption rate and new bone formation in response to scaffolds containing ACP compared to HA. 24,25 The aqueous solution of calcium chloride (1 wt%) and deionized water was then added to the organic phase (75% v) in six additions and mixed at 500 rpm for 2.5 min each to promote emulsification. The two HIPEs (BPO and TMA) were mixed at 2500 rpm for 30 s in the SpeedMixer to initiate crosslinking.…”
Section: Polyhipe Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported a significant increase in calcium ion release and subsequent osteoclast-mediated resorption rate and new bone formation in response to scaffolds containing ACP compared to HA. 24,25 The aqueous solution of calcium chloride (1 wt%) and deionized water was then added to the organic phase (75% v) in six additions and mixed at 500 rpm for 2.5 min each to promote emulsification. The two HIPEs (BPO and TMA) were mixed at 2500 rpm for 30 s in the SpeedMixer to initiate crosslinking.…”
Section: Polyhipe Fabricationmentioning
confidence: 99%
“…23 For this reason, many researchers have investigated the resorption rates of mixed calcium phosphate compositions with different percent crystallinities and assessed the effect on in vivo bone regeneration. 24,25 The relative ability of these calcium phosphate minerals to stimulate progenitor cell proliferation and differentiation is dependent on the physiological environment and presentation in the scaffold. In contrast, the demineralized bone matrix (DBM) stimulates bone growth by providing an environment in which invading progenitor and inflammatory cells are stimulated to release trophic cytokines to recruit cells for repair.…”
Section: Introductionmentioning
confidence: 99%
“…The different ions can be structured during the thermal (sintering or quenching) processes of the ceramic scaffolds, direct incorporation of ionic compounds can be obtained for the biopolymer scaffolds. Some pioneering works have shown the release of different levels of Ca ions from collagen gels, showing different effects on cell behaviors [152]. Sr ions were also incorporated into carboxymethylcellulose hydrogels as a bone scaffold to enable ionic stimulation of cells for bone formation.…”
Section: Control Of Therapeutic Ionsmentioning
confidence: 99%
“…More recently, Liu et al indicated that nano-HA-coated magnetic nanoparticles increased cell viability and guided neuronal growth (Liu et al, 2015). The releasing of Ca 2+ from Biphasic calcium phosphate bioceramics has been reported previously (Gallinetti et al, 2014;Seol et al, 2014). It has been hypothesized that the releasing of Ca 2+ from the hydrogel activated the purinergic receptor of mesenchymal stem cells, which induced neuronal differentiation (Glaser et al, 2013).…”
Section: Gene Expression At 3 Weeksmentioning
confidence: 94%